PENGARUH DAU, DAK FISIK DAN PAD TERHADAP INDEKS PEMBANGUNAN MANUSIA PADA PROVINSI KALIMANTAN BARAT - Herlambang Febriyanto (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The state presents various efforts and policies to realize people's welfare and become a developed nation, including through decentralization fund schemes such as the provision of General Allocation Funds and Physical Special Allocation Funds to local governments. In addition to receiving decentralization funds, local governments also have Regional Original Revenue as a source of funding to manage and improve the quality of the region and its people. Human development is one of the important aspects that determine the progress of a nation and is measured through the Human Development Index. This study intends to identify how far the influence of General Allocation Funds, Physical Special Allocation Funds and Regional Original Revenue on the level of progress of human development in 14 districts/cities in West Kalimantan Province for the 2017-2020 period. The research method is quantitative with panel data regression. The results of the analysis of this study reveal that the accumulation of General Allocation Funds, Physical Special Allocation Funds and Regional Original Revenue has a significant impact on the development of human quality. Human development is not significantly affected by DAU and Physical Special Allocation Funds when viewed from a separate aspect, while Regional Original Revenue has a significant effect.